(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: In the last 3 years outpatient installations have not been able to reach the specified patient satisfaction standard. The existence of a tiered BPJS system made the visit of the Medical Rehabilitation Poly to be poly with the most number of visits among other poly. After conducting the data survey at the beginning it was known that the patient’s satisfaction was still low at the Medical Rehabilitation Poly with 70% of patients stating that they were not satisfied with the facilities and services available. Objective: The purpose of this study was to analyze the respondents’ assessment of service convenience at the Medical Rehabilitation Center. Method: This study was analytic observational with a cross sectional approach. The population in this study were all patients at the Medical Rehabilitation Poly in 2017. The samples used were 333 respondents. The study was conducted using a questionnaire by asking questions directly to the respondents. Result: Based on service convenience dimensions, respondents rated decision convenience as good, very good access convenience, good transaction convenience, and good benefit convenience. There is only one variable that is poorly assessed, namely service waiting time in transaction convenience. Conclusion: The conclusion of this study is that respondents considered that service convenience in the Medical Rehabilitation Poly of Rumah Sakit Islam A. Yani Surabaya was good.